A unified method for maximal truncated Calderón–Zygmund operators in general function spaces by sparse domination. Issue 1 (22nd February 2020) - Anderson, Theresa C.; Hu, Bingyang
Abstract: In this note we give simple proofs of several results involving maximal truncated Calderón–Zygmund operators in the general setting of rearrangement-invariant quasi-Banach function spaces by sparse domination. Our techniques allow us to track the dependence of the constants in weighted norm inequalities; additionally, our results hold in ℝ n as well as in many spaces of homogeneous type.